PERKEMBANGAN KOLONISASI DI BELITANG PADA MASA PEMERINTAH HINDIA BELANDA TAHUN 1936-1942 - Ana Muttaqin; Kuswono Kuswono (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The objectives of this study are (1) to describe the mapping of the colonization area in Belitang in 1936-1942, (2) to describe the process of moving colonization in Belitang during the Dutch East Indies government in 1936-1942, (3) to describe the life of the Javanese colonists in Belitang. Belitang during the Dutch East Indies government in 1936-1942. Based on the existing problems, researchers are interested in studying more deeply the development of the Belitang colonization in 1936-1942. This is considered important because of the lack of research studies in the field of colonization development in Belitang in 1936-1942. As a researcher, of course, there is a need for a study in writing the history of colonization in Belitang. The method used is the historical method, which is a systematic framework for collecting historical sources. Collecting archives as research documents, both primary and secondary data. The results of research that has been done through the interpretation and writing of history. The results are in the form of both primary and secondary sources that researchers get. Collection of sources from Delpher, KITLV, as well as the Regional Library and Archives of Ogan Komering Ulu Timur Regency. the development of colonization in Belitang was able to reduce population density on the island of Java. Colonization in Belitang has progressed quite well, from an economic perspective, namely progress in the rice field sector, in the health sector by establishing three clinics, one school for education and an orderly system of regional government from Kurungan Nyawa village to Cahaya Negeri village.